Comparison of the effectiveness of manual cleaning, hydrogen peroxide vapour and ultraviolet-c in disinfection of hospital equipment : Usporedba učinkovitosti ručnog čišćenja, pare vodikovog peroksida i ultraljubičastog C zračenja u dezinfekciji bolničke opreme - Sedaghat, Yosra (Array, 2020)
Hospitals are the focus of many infections which cause the intensification of the patients’ illness and even their death. The number of bacteria on various hospital equipment was counted before and after being disinfected with manual cleaning (MC), hydrogen peroxide vapour (HPV) and ultraviolet-C (UV-C). The effectiveness of disinfection of hospital beds in intensive care unit (ICU) using the three methods MC, HPV and UV-C has been 66.67%, 100% and 50%, respectively. Hence, the effectiveness of HPV method in the disinfection of this unit has been higher than others. The effectiveness of otoscope disinfection in the ICU and blood pressure meter in the operating room with three methods of MC, HPV and UV-C has been 0%, 50% and 100%, respectively. So, for disinfecting these small outfits, UV-C method has proven to be the best one. In case of programming, the correct move of portable UV-Cs for complete coverage of massive equipment, disinfection with UV-C method may be considered more effective than other methods.